PRINSIP TOD MULTILEVEL SEBAGAI LANDASAN RENEWAL TERMINAL BUS LEUWIPANJANG - Andreas Tirta; Yohannes Karyadi Kusliansjah (Riset Arsitektur (RISA), 2022)
Abstract - Currently, the city of Bandung needs to fix its infrastructure and public transportation infrastructure in an effort to prepare for the presence of the high-speed rail which has a main station in Tegal Luar, the Gedebage area. With the presence of the high-speed rail in the city of Bandung, it will certainly affect the acceleration of the distribution of passengers and goods within the city. The intensity of this movement needs to be supported by transportation network infrastructure that can be well integrated, one of which is the implementation of the Multi-level Transit Oriented Development (TOD) system at Leuwipanjang Bus Station, Bandung. Leuwipanjang Bus Station still implements a single-level transportation service system, which means it is not efficient and effective enough to support the acceleration of planned public transportation services, especially multi-level-based public transportation as planned in the Bandung Urban Mobilty Project. This study aims to evaluate the design of Leuwipanjang Bus Station so that it becomes one of the TODs that is proper for being an extension of the public transportation infrastructure of the Tegal Luar public transportation which is a stop for the Bandung-Jakarta high-speed rail through an exploratory-analytic-comparative method that supports the Multi-Level concept. It was concluded that the condition of Leuwipanjang Bus Station requires adjustment to the presence of the Bandung-Jakarta high-speed rail which has an entrance at Tegal Luar Station, Gedebage. Keywords: infrastructure, public transportation infrastructure, multi-level TOD, Leuwipanjang Bus Station